AXEL Activity Monitor Phase 2 - Aranas, Raissa J.
Activity monitoring assists in the management of common diseases and medical operations such as cardiac, stroke, and post-surgery rehabilitation, obesity and diabetes, and energy expenditure calculations. The AXEL Activity Monitor Project is the first low cost and efficient physical activity monitor in the Philippines. AXEL Phase 1 produced an Activity monitoring system which has 3 components: AXEL monitor (the data acquisition), AXEL reader (data transfer to computer) and AXEL viewer (GUI). The AXEL Phase 2 project aims to remove existing shortcomings of the Axel Activity Monitor. This project improves battery life (using the Z8 Encore! Halt Mode) for effective monitoring of the patient's activity. It will also implement the FAT16 File Format for the MMC and store data in a Comma Separated File (CSV) format for faster data transfer and interpretation. Another improvement is an alarm which triggers when a strenuous activity has been detected from the patient wearing the AXEL Monitor. It also aims to enhance user (both patient and doctor) interface, robust packaging, and reduction of design costs. The AXEL viewer will have more functions which include activity classification display, comment toolbar, patient information, and goal information display. For the activity classification, features that will be extracted from the accelerometer data are: mean, energy, standard deviation, and correlation of the axes' acceleration data. A trained neural network will use the extracted features to match the accelerometer data to a corresponding activity.